'Shooting your voice': challenging power relations at school through Photovoice. Issue 6 (2nd November 2022) - Hemy, Avy Dwight; Meshulam, Assaf
ABSTRACT: Despite the popularity of student voice initiatives, there is ample evidence that they fail to challenge power relations at school or help marginalized students make their voices heard. This paper presents a student voice project based on the Photovoice method. The project was implemented with marginalized youth in an urban high school in Israel. Findings show that students experienced significant improvement in their self-confidence and self-esteem and in their ability to engage in dialogue with the school administration in a way that altered their school life, yet they remained skeptical regarding their ability to change power relations at school.